GAMBARAN MASALAH KEPERAWATAN PSIKOSOSIAL PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA (PSTW) KHUSNUL KHOTIMAH PEKANBARU - Al Rasyid, Harun "; ", Jumaini "; Karim, Darwin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Psychosocial is any condition or event that can change a person's life, and the concerned are  required to be able to adapt  to changes. This study design was descriptive survey which aim to see how the overview of the psychosocial issues that occur to elderly in PSTW Khusnul Khotimah. Samples in this study were 42 respondents living in PSTW Khusnul Khotimah taken by purposive sampling technique. The instrument used in this study was the Geriatric Depression Scale (GDS) which has been modified and has been tested for validity and reliability. The results of the study discusses the characteristics such as gender, age, education level, work experience, illness, and marital status. Psychosocial issues divided into 4 subvariable, with the results obtained for each showed from 42 respondents surveyed, 30 respondents (71.4%) had moderate self esteem low, 28 respondents (66.7%) had  a severe helplessness, 24 respondents (57.1%) had mild despair, and 31 respondents (73.8%) had a moderate social isolation. The appropriate of nursing management to change these elderly psychosocial become the main suggestion for the creation of coping well to physiological changes in the elderly.Key word : low self esteem, powerlessness,hopeless, social isolation, elderly, psychosocial